Industria de bioinsumos de uso agrícola en Colombia - Zambrano-Moreno, Diana Corina; Ramón-Rodríguez, Luisa Fernanda; Van Strahlen-Pérez, Mario; Bonilla-Buitrago, Ruth Rebeca (My University, 2015)
Bio-products are primarily produced by using plant growthpromoting bacteria. This group of microorganisms is composed of different genera with the capability to stimulate plant growth increasing their productivity and promoting bio-control. The use of such microorganisms in Colombian agriculture has been highlighted to generate significant changes in production systems. The industry of bio-products was characterized using three parameters: i. records of bioproducts at the Colombian Agricultural Institute -ICA, ii. the patents recorded at the Superintendence of Industry and Commerce -SIC and iii. the Accession request to the genetic resources tool at the Ministry of Environment, Housing and Territorial Development - MADS, within 2004-2011. One hundred eleven records of bio inoculants were found in Colombia, destined mainly to ornamental crops (24.7%), vegetables (16.3%), and cereals (13.2%). At patent level thirteen ones were identified, nine found in the International Patent Classification IPC - recognized by the Organization for Economic Cooperation and Development - OECD. The access to the database of MADS genetic resource allowed to identify 16 applications. Only one microorganism Bacillus thuringiensis was registered at all the assessed institutions. It was concluded that the development of bio-products in Colombia is only emerging in the encouragement research of the use of the microbial biodiversity, as well as the processes regarding patent register of production processes.

Los bioinoculantes son producidos principalmente a partir de bacterias promotoras de crecimiento vegetal. Estos microorganismos agrupan diferentes géneros, con capacidad de estimular e incrementar el crecimiento, la productividad vegetal y controlar otros organismos. El uso de este tipo de microorganismos, en la agricultura colombiana, tiene potencial para generar transformaciones importantes en los sistemas productivos. En este trabajo, la industria de bioinsumos en Colombia fue caracterizada a partir de tres parámetros i. el análisis de los registros ante el Instituto Colombiano Agropecuario – ICA, ii. las patentes solicitadas ante la Superintendencia de Industria y Comercio - SIC y, iii. la solicitud de acceso a recurso genético, desde el 2004 hasta el año 2011ante el Ministerio de Ambiente y desarrollo sostenible -MADS. En Colombia, se encontraron 111 registros de bioinsumos, destinados, principalmente, a cultivos ornamentales 24,7%, hortalizas 16,3% y cereales 13,2%. A nivel de patentes, se identificaron 13, de las cuales, 9 se encuentran dentro de la Clasificación Internacional de Patentes - IPC - reconocidas por la Organización para la Cooperación y el Desarrollo Económicos -OCDE- . La base de datos de acceso a recurso genético del MADS permitió identificar 16 solicitudes. Sólo un microorganismo (Bacillus thuringiensis) tuvo registro en las tres instituciones. El estudio permitió concluir que el desarrollo de bioinsumos en Colombia es incipiente, en el ejercicio de estimular investigación para el uso de la biodiversidad microbiana, así como los procesos de registro de patentes, alrededor de los procesos de producción.
Bioinoculants industry for agricultural use in Colombia
Artículo científico
Keywords: Bacterias; Agricultura sostenible; Sostenibilidad; Biodiversidad; Microorganismos; Cultivos; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Horticulture; Recursos genéticos; Sustainable agriculture; Sustainability; Biodiversity; Microorganisms; Crops; Genetic resources